Modeling the mediating role of trust in halal cosmetics: Evidence from MS Glow consumers in Palopo City‎ - Ali, Linda A.; Ahmad Syarief Iskandar; Ishak, Ishak (Journal of Islamic Economics Lariba, 2025)
IntroductionThe halal cosmetics industry in Indonesia is experiencing significant growth, driven by increasing consumer awareness of sharia compliance, safety, and ethical values. Yet, empirical studies on how halalness, service quality, and price interact with consumer trust and satisfaction remain limited, particularly in non-metropolitan contexts such as Palopo City, Indonesia.ObjectivesThis study aims to analyze the influence of product halalness, service quality, and price on consumer satisfaction of MS Glow cosmetics in Palopo City, with consumer trust examined as a mediating variable.MethodThe research employed a quantitative approach using a structured questionnaire distributed to 163 MS Glow users aged 18–45 years in Palopo. Data were analyzed through Structural Equation Modeling with the Partial Least Squares technique. Measurement validity and reliability were assessed using factor loadings, average variance extracted, and reliability indices.ResultsThe findings demonstrate that halalness, service quality, and price all have significant positive effects on consumer trust, while trust itself strongly enhances satisfaction. Furthermore, trust mediates the relationship between the three antecedents and consumer satisfaction. Among the predictors, halalness is the strongest determinant of trust, underscoring its central role in shaping consumer evaluations in a Muslim-majority context.ImplicationsThe study highlights the strategic importance of building trust through transparent halal assurance, consistent service performance, and fair pricing. These factors collectively enhance consumer satisfaction and provide actionable insights for managers in the halal cosmetics sector.Originality/NoveltyThis research contributes by extending the study of halal marketing into a non-metropolitan Indonesian setting and by clarifying the mediating role of trust. It enriches the literature by empirically establishing that halalness, beyond price and service quality, is the most influential driver of consumer trust and satisfaction in halal cosmetics.